ANALISIS YURIDIS KEDUDUKAN AKTA IZIN ROYA HAK TANGGUNGAN SEBAGAI PENGGANTI SERTIFIKAT HAK TANGGUNGAN YANG HILANG - ARNOVI AYU (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Prof. Dr. Syafruddin Kalo, SH, MHum3. Prof. Dr. Saidin, SH, MHum Elimination of hypothecation according to Article 18, paragraph 1 requires hypothecation cancellation. it is done when the debt guaranteed in the contract is paid off. One of its requirements is the existence of land rights certificate and hypothecation certificate for elimination. When it loses, it will be substitued by hypothecation cancellation permit deed or cancellation consent as the prerequisite from the Land Office to process the cancellation. Hypothecation cancellation permit deed is a notification letter made by a Notary which states that hypothecation certificate has been missing. However, it is not regulated clearly and specifically in any law or regulations. The research problems are how about legal consideration for a Notary to make hypothecation cancellation permit deed, how about the procedure and the process of mnaking it, and how about its position. Keywords: Cancellation Permit Certificate, Cancellation Consent, Hypothecation Certificate